The effects of vitamin D supplementation on interictal serum levels of calcitonin gene-related peptide (CGRP) in episodic migraine patients: post hoc analysis of a randomized double-blind placebo-controlled trial - Zeinab Ghorbani; Pegah Rafiee; Akbar Fotouhi; Samane Haghighi; Reyhaneh Rasekh Magham; Zeynab Sadat Ahmadi; Mahmoud Djalali; Mahnaz Zareei; Soodeh Razeghi Jahromi; Sahar Shahemi; Maryam Mahmoudi; Mansoureh Togha (The Journal of Headache and Pain, 2020)
Abstract Background Emerging evidence showed promising effects of vitamin D on headaches characteristics. Thus, it seems there is still a need for more researches to clarify the mechanisms by which this vitamin exerts anti-migraine effects. Methods The present study was conducted as a 16-week randomized double-blind placebo-controlled trial on 80 episodic migraine patients allocated in 2 parallel groups each consisted of 40 patients who received vitamin D 2000 IU/d or placebo. At baseline and after the intervention completion, headache diaries and migraine disability assessment questionnaire (MIDAS) were used to assess migraine related variables in patients. Also, interictal serum concentration of calcitonin gene-related peptide (CGRP) (as the dominant mediator of migraine pain pathogenesis) was evaluated using ELISA method. Results The mean (SD) of age in the vitamin D and placebo groups was 37 (8) and 38 (12) years, respectively. ANCOVA test adjusted for baseline values, and confounders showed vitamin D supplementation resulted in a significant improvement in MIDAS score after 12 weeks in the intervention group (21.49 (16.22–26.77)) compared to placebo (31.16 (25.51–36.82) P value: 0.016). Moreover, after controlling for baseline levels, and other variables using ANCOVA, CGRP level was appeared to be significantly lower following vitamin D supplementation (153.26 (133.03–173.49) ng/L) than the patients in the placebo arm (188.35 (167.15–209.54) ng/L) (P value = 0.022). Conclusion According to the current findings, vitamin D supplementation in episodic migraineurs, particularly in those with migraine with aura, may potentially improve migraine headache characteristics and disability probably through attenuating CGRP levels. Therefore, these results could provide a new insight into anti-nociceptive effects of vitamin D; however, more studies are required to confirm our findings. Trial registration The trial is registered in the Iranian registry of clinical trials (IRCT) at 11 July 2018, with IRCT code: IRCT20151128025267N6 .